Drosophila CRY is a deep brain circadian photoreceptor. - Emery, P.; Stanewsky, R.; Helfrich-Forster, C.; Emery-Le, M.; Hall, J.C.; Rosbash, M. (Neuron, 2000)
cry (cryptochrome) is an important clock gene, and recent data indicate that it encodes a critical circadian photoreceptor in Drosophila. A mutant allele, cry(b), inhibits circadian photoresponses. Restricting CRY expression to specific fly tissues shows that CRY expression is needed in a cell-autonomous fashion for oscillators present in different locations. CRY overexpression in brain pacemaker cells increases behavioral photosensitivity, and this restricted CRY expression also rescues all circadian defects of cry(b) behavior. As wild-type pacemaker neurons express CRY, the results indicate that they make a striking contribution to all aspects of behavioral circadian rhythms and are directly light responsive. These brain neurons therefore contain an identified deep brain photoreceptor, as well as the other circadian elements: a central pace-maker and a behavioral output system.